Decreased reproductive performance in xCT-knockout male mice. (3rd October 2017) - Hamashima, Shinji; Homma, Takujiro; Kobayashi, Sho; Ishii, Naoki; Kurahashi, Toshihiro; Watanabe, Ren; Kimura, Naoko; Sato, Hideyo; Fujii, Junichi
Abstract: Sulphoxidation occurs in protamines that are enriched in cysteine and supplies chromatin for packaging. The extracellular fluid contains higher levels of oxidised cysteine (cystine), and some cells utilise system xc −, a cystine transporter in which xCT is the main protein component, to fulfil the need for cysteine. We hypothesised that system xc − might ensure the supply of cysteine needed for spermatogenesis. The reproductive ability of xCT −/− male mice at 6- to 18-weeks of age appeared to be lower than xCT +/+ male mice. The courtship behaviour of the xCT −/− male mice was undynamic, which appeared to be associated with the low reproductive ability of xCT −/− male mice. xCT was found to be expressed in mouse testes, notably in Sertoli cells, as well as in the epididymis and the levels were increased at the time of sexual maturation. Despite the normal histological appearance of testicular tissues, the cauda epididymis of xCT −/− mice contained round, greater numbers of immature spermatogenic cells than that of xCT +/+ mice. However, there were no significant differences in the numbers of sperm stored in the cauda epididymis or in the concentrations of cysteine or glutathione in the testes. The resulting sperm had normal fertilising ability. Thus, system xc − appears to function as a backup system for supplying cysteine to testes and play a pivotal role in supplying cysteine for normal sexual behaviour by a mechanism that is different from that for the supply of cysteine in spermatogenesis.